ANALISIS FAKTOR YANG MEMPENGARUHI PEMILIHAN OBAT GENERIK DI APOTEK KARANGAJI KEDUNG JEPARA - Sabiq Ismil Adhom; Zaenal Fanani; Intan Adevia R (Yayasan Nusantara Hasana Berdikari, 2025)
The public's selection of generic drugs is still often influenced by negative perceptions regarding their quality and effectiveness compared to branded drugs. In fact, pharmacologically, generic drugs contain the same active ingredients and are more affordable. This study aims to analyze the factors influencing the selection of generic drugs at Karangaji Pharmacy, Kedung Subdistrict, Jepara Regency. The research employed a quantitative approach with a descriptive-analytic design and a cross-sectional method. A sample of 96 respondents was determined using the Slovin formula from a population of 2,260 patients. The research instrument was a Likert scale questionnaire covering four independent variables: price, quality, socio-cultural factors, and recommendations from pharmaceutical personnel. Data analysis was conducted using the Chi-Square test, independent sample t-test, and Pearson correlation through SPSS. The results showed that socio-cultural factors were the most dominant in influencing the selection of generic drugs, as proven significant in the t-test (p < 0.001) and Pearson correlation (p = 0.012). Recommendations from pharmaceutical personnel also had a significant effect (p = 0.014). Price was only significant in the t-test (p = 0.040), while quality did not show a significant effect in any of the statistical tests. In conclusion, the public’s decision to choose generic drugs is more strongly influenced by social aspects and educational support from pharmaceutical personnel rather than price or perceived quality. Therefore, effective public education and community-based approaches are necessary to increase the rational acceptance and use of generic drugs in the community.